Analisis Kepuasan Konsumen Terhadap Kualitas Produk Dan Layanan Pada Mie Gacoan Jimbaran Kabupaten Badung Bali - Wati, Asma; Suryawan Wiranatha, Anak Agung Putu Agung; Bayu Sadyasmara, Cokorda Anom (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2023)
Mie Gacoan is a culinary business that is currently experiencing development, especially in the Bali area. This makes the manager of Mie Gacoan have to choose a suitable strategy to be able to survive with competitors. This study aims to determine the quality attributes of products and services that are considered important and analyze the level of conformity of expectations and overall consumer satisfaction with the quality of products and services and determine the attributes that need to get priority from Mie Gacoan in order to maintain and increase consumer satisfaction. The methods used are Importance Performance Analysis and Customer Satisfaction Index. The sampling technique in this study was purposive sampling. The results showed that the attribute of the highest degree of conformity in product quality was the variety of the beverage menu by 101.21% and the attribute of the lowest degree of conformity was the level of food maturity of 86.22%. The attributes of the highest degree of conformity to the quality of service are Toilet cleanliness by 98.36% and neat appearance of employees with a degree of conformity of 98.26%. While the lowest attribute is the Timeliness of presentation of 83.29%. The attributes that must be prioritized are the attributes contained in quadrant A, namely the level of maturity of food and beverage taste for product quality, while the attributes of service quality are Punctuality of serving, Speed of employees in serving consumers and Dexterity of cashiers in serving consumers. The CSI results showed that all attributes of product and service quality were considered very important by consumers with an average number of MIS values greater than 4.20 and a consumer satisfaction rate of 81.65% with the category of very satisfied for product quality and 79.21% with the category of satisfied for service quality .